Reconciling a positive ecological balance with human development: A quantitative assessment - Lucia Tamburino (Elsevier, 2021)
Clear indicators and evaluation criteria are essential to keep humanity’s environmental impact within planetary boundaries. We introduce a new criterion based on two constraints, accounting for both ecological and human sustainability. The ecological constraint is defined through a novel indicator, the eco-balance, grounded on the well known concept of ecological footprint and the new concept of population biodensity. The human sustainability constraint is based on the estimated level of biocapacity consumption needed to achieve an acceptable level of human development. The application of our criterion to world countries shows where technological improvements and changes in consumption patterns are sufficient to reach sustainability, and where actions on population and/or restoring ecological capital are also needed. This highlights synergic patterns going beyond simplistic schemes, such as overconsumption vs. overpopulation or developed vs. developing countries.